Association between postmortem computed tomography value of cerebrospinal fluid and time after death: A longitudinal study of antemortem and postmortem computed tomography. (January 2023) - Fujimoto, Kotaro; Gonoi, Wataru; Ishida, Masanori; Okimoto, Naomasa; Nyunoya, Keisuke; Abe, Hiroyuki; Ushiku, Tetsuo; Abe, Osamu
Abstract: This study was designed to examine the antemortem factors affecting cerebrospinal fluid (CSF) Hounsfield Units (HU) on postmortem computed tomography (PMCT) compared to the antemortem CT (AMCT). Fifty-five participants without brain lesions who died at a university hospital and underwent AMCT, PMCT, and an autopsy were enrolled. We recorded age, sex, time after death, the CSF HU on AMCT and PMCT at multiple measuring points, 4-point-scale brain atrophy grade on AMCT, and the cella media index. We tested the effects of CSF HU factors observed on PMCT. No significant differences were observed between CSF HUs at any of the PMCT measurement points. The average CSF HU on PMCT was positively correlated with the natural logarithm of the time after death (Pearson's correlation coefficient, 0.81; p  < 0.001). No other factors showed correlative relationships. Up until approximately 12 h after death, the CSF HU on PMCT depended only on the time since death.